What contributes to total factor productivity growth in the Chinese banking sector? - Zhu, Ning; Zhang, Ning; Wang, Bing; Baležentis, Tomas (Technological and Economic Development of Economy, 2018)
We propose a new metafrontier, non-radial, biennial Luenberger productivity indicator to evaluate the total factor productivity growth of the Chinese banking sector, during the period of 2004–2012. The bootstrapping approach is also taken into account to introduce the statistical inference of the total factor productivity, and its components. It is found that the overall Chinese banking sector operated well with an average growth rate of 5.4%, where technological progress was the driving force promoting the development of the Chinese banking sector during the earlier studied period, and efficiency gains outperformed technological progress during the later studied period. We investigated three banking groups, state-owned commercial banks and joint-stock commercial banks depending on their technological progress, but city commercial banks were dominated by efficiency gains. Regarding the productivity growth gap, the metafrontier productivity growth gap and efficiency change gap appeared to show gradual convergences, but the technological change gap maintained the width at a certain extent.